2020
DOI: 10.3390/bs10030064
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-Compassion and Sleep Quality: An Overview of a Seven-Year German Research Program

Abstract: Poor sleep quality is highly prevalent in modern societies and negatively linked to various health outcomes. While previous research has demonstrated preliminary evidence for self-compassion as a tool for improving sleep quality, this review provides a meta-analysis of respective published and unpublished results of our own research group using German samples. A total of nine studies are included (N = 956 participants), consisting of both correlational and experimental data. Across these studies, there was a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…self-critical standards) that can maintain the cycle of basic psychological need frustration and illbeing over time (Soenens et al, 2008). Critically, research has revealed associations between sleep disturbance and perceived stress (Morin et al, 2003), heavy alcohol use (Britton et al, 2020), and less self-compassion (Butz & Stahlberg, 2020)…”
Section: Self-determination Theorymentioning
confidence: 99%
“…self-critical standards) that can maintain the cycle of basic psychological need frustration and illbeing over time (Soenens et al, 2008). Critically, research has revealed associations between sleep disturbance and perceived stress (Morin et al, 2003), heavy alcohol use (Britton et al, 2020), and less self-compassion (Butz & Stahlberg, 2020)…”
Section: Self-determination Theorymentioning
confidence: 99%
“…When adolescents with a high level of resilience, self-compassion, and hope face problems or challenges, they will experience a certain process of accepting the situation in a calm, balanced, and meaningful way. Adolescents also experience positive emotions, a sense of security and comfort, and a soothing effect, as well as improvement in negative feelings related to problems in performing healthy lifestyle behavior (Butz & Stahlberg, 2020;Li et al, 2019;Nery-Hurwit et al, 2018).…”
Section: The Relationship Between Resilience Self-compassion and Hope...mentioning
confidence: 99%
“…Two meta-analyses have examined the relationship between self-compassion and sleep ( Brown et al, 2021 ; Butz and Stahlberg, 2020 ). Brown et al (2021) found that among adults ( N = 1830) self-compassion was negatively associated with disturbing sleep symptoms ( r = −0.32, 95% CI [−0.36, −0.28]) with effect sizes ranging from −0.37 ( Dvořáková et al, 2017 ) to −0.23 ( Hu et al, 2018 ) among college students.…”
Section: Self-compassion and Sleep Qualitymentioning
confidence: 99%
“… Brown et al (2021) found that among adults ( N = 1830) self-compassion was negatively associated with disturbing sleep symptoms ( r = −0.32, 95% CI [−0.36, −0.28]) with effect sizes ranging from −0.37 ( Dvořáková et al, 2017 ) to −0.23 ( Hu et al, 2018 ) among college students. Butz and Stahlberg (2020) found that among community adults ( N = 959) self-compassion was positively related to subjective sleep ( r = 0.30, 95% CI [0.24, 0.36]). Compared to a control condition, self-compassion interventions ( n = 3) led to increases in sleep quality (Hedges’ g = 0.48, 95% CI [0.15, 0.82]; Butz and Stahlberg, 2020 ).…”
Section: Self-compassion and Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation